Crack initiation of neutron-irradiated 304 L stainless steel in PWR primary water. (December 2021) - Du, Donghai; Sun, Kai; Was, Gary S.
Abstract: Stress corrosion crack (SCC) initiation of neutron-irradiated 304 L stainless steel was studied following irradiation to various doses. Tensile test results show that SCC susceptibility dependence of the alloy on dose is slight. Grain boundary (GB) oxidation was observed prior to crack initiation and DCs always proceeded before or accompanies crack initiation in the bend test. The DC-GB intersections were the predominant crack initiation sites due to the high local stress. Constant load tests resulted in greater GB oxidation and cracks initiated at applied stress as low as 50% of the irradiated yield strength due to the long exposure time. Highlights: 304 L showed no strong IASCC dependence on dose in the range of 5.4–125.4 dpa. Crack initiated at stresses well below yield with a stress threshold of 0.5σy . Grain boundary oxidation is a necessary step of crack initiation. Dislocation channels formed at stresses below yield and enhanced GB oxidation.